Effects of low voltage electrical stimulation during bleeding and hot boning on beef loin eye and top round muscles - J.B. Axe; Melvin C. Hunt; Donald H. Kropf; D.G. Gray; Curtis L. Kastner; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1984)
Our study evaluated the effects of low voltage electrical stimulation (ES) during bleeding and hot boning at 1 hr postmortem on loin eye (LE) and top round (TR) muscles. Possibly because of relatively slow initial chilling rate used in our study, hot-boned (HB) muscles, even without ES, were comparable to conventionally chilled and boned counterparts. In fact, coupling ES with HB proved less desirable than HB only.
Keywords: Cattlemen' s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Electrical stimulation; Hot boning; Loin eye; Top round